Writing a winning FRGS proposal - Abdullah, Moha Asri (2019)
Writing a winning research proposal for Fundamental Research Grant of the Malaysian Ministry of Education is not always easy. Many applicants even could not secure the grants. There have been numerous approaches used by different academicians. Similarly, various seminar on have been conducted to generate competitive research proposal to secure the grants. However, there has been no consensus on how to prepare successful research proposal among scholars and policy makers. In view of this, the paper addresses the issue by observing certain guidelines provided by the grant providers as a way to successfully prepare a competitive research proposal. In this relation, Fundamental Research Grant Scheme (FRGS) is not exceptional to this that understanding the criteria required is a fundamental factor to secure the grant.